Procopius on the Religion of the Early Slavs: Comparison with Other Barbarians - Drapelova, Pavla Gkantzios (Studia Ceranea, 2021)
The works of Procopius of Caesarea are generally perceived as one of the earliest and main Byzantine sources on culture of the early Slavs. Its various passages have repeatedly become subject of numerous interpretations and hypotheses. The present article adopts a different approach to this material and compares the information on the religion of the Sclavenes and the Antes with the beliefs of other barbarian groups mentioned by Procopius. The study demonstrates that the sentences on early Slavic religion are rather unique in Procopius’s works especially in respect to the variety of his topics. Furthermore, the evidence indicates that the most similar elements in his descriptions of religious practices connect the early Slavs and the inhabitants of the island of Thule. This does not mean, however, that they were perceived as related by Procopius as there are no similarities in the description of other cultural specificities. The textual evidence nevertheless indicates that Procopius described the religious practices of these two groups in similar terms.